Distribution of Lgr5‐positive cancer cells in intramucosal gastric signet‐ring cell carcinoma. Issue 9 (September 2016) - Nakajima, Tomoyuki; Uehara, Takeshi; Maruyama, Yasuhiro; Iwaya, Mai; Kobayashi, Yukihiro; Ota, Hiroyoshi
Abstract : Leucine‐rich repeat‐containing G‐protein‐coupled receptor 5 ( Lgr5 ) is a putative intestinal stem cell marker that is also expressed in various tumors. To analyze its pathological characteristics in mucosal gastric signet‐ring cell carcinoma (SRCC), we investigated Lgr5 expression in 35 intramucosal gastric SRCC patients using RNAscope, a newly developed RNA in situ hybridization technique. Lgr5 expression in individual tumor cells was scored semi‐quantitatively from 0 to 400. Ki67 was also examined by immunohistochemistry, with a linear arrangement of Ki67‐expressing cells present in 20 of 35 cases. This area of Ki67‐expressing cells was topographically divided into upper, middle, and lower regions. All cases with linear Ki67 expression patterns also had Lgr5 ‐positive cells arranged in a linear fashion in the lower area—which was distinct from the area of high Ki67 expression. The rate of Ki67 positivity in Lgr5 ‐positive cells was significantly lower than that of Lgr5 ‐negative cells in areas of high Ki67 expression. In intramucosal SRCC, the low mitotic activity of Lgr5 ‐positive cells suggests that they may represent cancer stem cells as seen in other types of stomach carcinomas. Intramucosal SRCC may therefore contain stem cells expressing Lgr5 in the lower area of the lamina propria, akin to normal gastric pyloric mucosa.